Hubungan Frekuensi Konsumsi Fast Food dan Durasi Tidur Dengan Status Gizi Pada Siswa SMA Negeri 6 Kota Palu - Trisya Widya Tanti; Ni Ketut Kariani; Nuristha Febrianti (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Adolescence is an important phase characterized by physical and behavioral changes, including diet and sleep, which can affect nutritional status. Frequency of fast food consumption and sleep duration are two factors that are thought to contribute to the imbalance of adolescent nutritional status. The purpose of this study was to analyze the relationship between the frequency of fast food consumption and sleep duration with nutritional status in students of SMA Negeri 6 Palu City. This study uses a quantitative approach with cross-sectional design. The population in this study active students in SMA Negeri 6 Palu city from Grade 10 to Grade 12 amounted to 841 students, with a Simple Random Sampling technique, : the results showed that most respondents were female (64.8%), age 16 years (51.7%), as many as (47.2%) students included in the category always consume fast food and (46.1%) have more sleep duration. Most nutritional Status is in the category of over nutrition (39.3%). There was a relationship between fast food consumption and nutritional status (p = 0.010) and there was no relationship between sleep duration and nutritional status (p = 0.813).